How to Design a Perfect City. - Cass, S. (IEEE spectrum)
This paper presents one of Paolo Soleri's latest concepts, the Lean Linear City. Designed for the burgeoning urban populations of China, it stretches for hundreds of kilometers along the spine of a high-speed rail corridor to form a continuous structure in which people live, work and play. Photovoltaic cells and windmills help power the city